Comparing Wi-Fi 6 and 5G Downlink Performance for Industrial IoT - Roberto Maldonado; Anders Karstensen; Guillermo Pocovi; Ali A. Esswie; Claudio Rosa; Olli Alanen; Mika Kasslin; Troels Kolding (IEEE Access, 2021)
The use of wireless communications in Industrial Internet of Things (IIoT) enables unparalleled levels of flexibility and instantaneous reconfiguration for autonomous industrial processes. In this paper, the focus is on optimizing and evaluating Wi-Fi 6 and 5G New Radio (NR) licensed and unlicensed wireless networks for meeting the packet latency and reliability requirements of critical IIoT applications. The study is based on extensive system simulations using a 3GPP-defined IIoT indoor factory framework and application traffic models. Each radio technology is individually optimized leveraging the pros and cons of that technology to maximize the carried load in the network while fulfilling the delay requirements at a specified reliability level of 99.999 %. In addition to a performance comparison, the paper also provides deployment guidance for applying each radio technology in the considered IIoT setting. With proposed latency aware scheduling and when operated in interference free spectrum, Wi-Fi 6 can support <1 ms applications at a very low load, whereas the performance gap with respect to 5G NR reduces as delay requirements are relaxed to 10–100 ms. Conditioned on the fulfilment of the application latency and reliability requirements, unlicensed 5G NR shows nearly $2× $ the spectral efficiency of Wi-Fi 6 in all available configurations. Licensed 5G NR shows generally the best performance, especially for delay requirement <1 ms, supporting 2–4 $× $ the spectral efficiency achievable by unlicensed technologies.